High-sensitivity infrared attenuated total reflectance sensors for in situ multicomponent detection of volatile organic compounds in water - Lu, Rui; Li, Wen-Wei; Mizaikoff, Boris; Katzir, Abraham; Raichlin, Yosef; Sheng, Guo-Ping; Yu, Han-Qing (Nature protocols, 2016)
Volatile organic compounds (VOCs) are by-products of human activity that are particularly difficult to detect in water. This protocol describes an infrared chemical sensing device for enriching and detecting VOCs via attenuated total reflection spectroscopy. In situ detection of volatile organic compounds (VOCs) in aqueous environments is imperative for ensuring the quality and safety of water supplies, yet it remains a challenging analytical task. We present a high-sensitivity method for in situ analysis of multicomponent VOCs at low concentrations based on the use of infrared attenuated total reflection (IR-ATR) spectroscopy. This protocol uses a unique ATR waveguide, which comprises a planar silver halide (AgCl x Br 1− x ) fiber with cylindrical extensions at both ends to increase the number of internal reflections, and a polymer coating that traps VOCs and excludes water molecules. Depending on the type of VOC and measurement scenario, IR spectra with specific frequency windows, scan times and spectral resolutions are obtained, from which concentration information is derived. This protocol allows simultaneous detection of multiple VOCs at concentrations around 10 p.p.b., and it enables accurate quantification via a single measurement within 5 min without the need for sample collection or sample pretreatment. This IR-ATR sensor technology will be useful for other applications; we have included a procedure for the analysis of protein conformation changes in Supplementary Methods as an example.